2018
DOI: 10.3390/app8122333
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Analyses on Multiscale Structural and Mechanical Properties of ε-Si/GeSi/C-Si Materials

Abstract: Strained silicon (ε-Si) is a promising material that could extend Moore's law by enhancing electron mobility. A ε-Si material is usually composed of multiscale, multilayer heterostructures, where the strained-silicon film or strap is tens-of-nanometers thick, and its buffer layers are of the micrometer scale. The structural properties determine the electrical performance and reliability of ε-Si-based devices. Inhomogeneous residual stress is induced during the preparation, which induces ε-Si structure failure.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…There are two approaches to integrating Ge with SOI. One way is to use bulk Ge or a Ge x Si 1−x alloy, matched to a Si substrate through a layer with a gradually increasing proportion of Si in Ge x Si 1−x [171]. This offers the possibility of tuning the bandgap from the one found in bulk Si to the one of bulk Ge [172].…”
Section: The Case For Hybrid Si Integration For Mm-wave Generationmentioning
confidence: 99%
“…There are two approaches to integrating Ge with SOI. One way is to use bulk Ge or a Ge x Si 1−x alloy, matched to a Si substrate through a layer with a gradually increasing proportion of Si in Ge x Si 1−x [171]. This offers the possibility of tuning the bandgap from the one found in bulk Si to the one of bulk Ge [172].…”
Section: The Case For Hybrid Si Integration For Mm-wave Generationmentioning
confidence: 99%
“…Zhang et al present a demodulation technique for weak photo-acoustic signals of laser interferometer on water surface [40]. The last paper was written by Qiu et al on the experimental analyses on multiscale structural and mechanical properties of ε-Si/GeSi/C-Si materials [41]. Strained silicon (ε-Si) is a promising material that could extend Moore's law by enhancing electron mobility.…”
Section: Other Measurement Systemsmentioning
confidence: 99%
“…Micro-Raman spectroscopy (MRS) is an effective method to achieve high-resolution [ 6 , 7 ] and nondestructive [ 8 , 9 , 10 ] detection of stress in materials. Early studies of light-scattering behavior in condensed matter physics found that the Raman spectra of a variety of crystal materials were affected by stress/strain.…”
Section: Introductionmentioning
confidence: 99%